Estimation of an aerosol source in forced ventilation through prior identification of a convolutive model. (May 2017) - Chata, Florent; Belut, Emmanuel; Maillet, Denis; Keller, Francois-Xavier; Taniere, Anne
Highlights: Linear differential systems with time constant coefficients have convolutive solutions. Transient concentration response to a pollutant source in a ventilation configuration is considered. The method requires a prior calibration experiment before estimation of the source. Identification of the transfer function, with regularization, also provides its steady state version. Validation of the method is made on a real experimental configuration. Abstract: This article presents a method for estimating the time dependent generation rate of an aerosol source starting from a transient concentration signal measured at a distant point. The method is made up of two distinct steps: a calibration phase, followed by an estimation phase. The calibration phase consists in identifying a transfer function (termed "impedance") between a known source (the "calibration source") and its measured concentration response. In the second step the unknown source generation rate, in the configuration of interest, is estimated by inversion of the corresponding measured concentration signal at the same point, using the previously identified impedance. The time integral of this generation rate, the emitted aerosol dose, can be calculated directly, starting from the integral of the (transient) impedance. Here both simulation of inversions and application to a real experiment have been implemented. The results confirm that it is possible to estimate the temporal pattern of injection and the global emitted mass of pollutant.